Level of Environmental Friendliness of Bottom Gillnet Fishing Gears in Krueng Raya, Sabang City - Rizka Maula (Journal Informatic, Education and Management (JIEM), 2026)
Bottom gillnets is one of the most commonly used fishing gear by fishermen because of its ease of use and relatively affordable investment costs. The use of this fishing gear has the potential to cause negative impacts on the aquatic environment. The purpose of this study is to analyze the environmental friendliness of bottom gillnets at Krueng Raya Fish Landing Place in Sabang City. The research method was conducted through observation and structured interviews with fishermen based on a scoring system for the environmental friendliness of fishing gear. The sampling method in this study used purposive sampling. The results of the study indicate that bottom gillnets are classified as less environmentally friendly fishing gear. The main problem occurs due to the low selectivity of fishing gear towards the catch.